(untitled) (Faridpur Medical College Journal, 2020)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive disease and there is not yet a cure. Not only in Bangladesh but also worldwide the incidence of COPD is increasing. The disease is associated with some metabolic derangement such as electrolytes imbalance. Those factors further worsen the disease course. As a result COPD related morbidity, mortality and cost to health systems are also increasing. This cross-sectional observational study was conducted in Faridpur Medical College Hospital (FMCH) over 6 months among 100 patients who were admitted with acute exacerbation of COPD. The mean age was (58.13 ± 9.96) years. In this study serum electrolytes were found below the normal range in 68 (68%) cases and within normal range in 32(32%) cases. Isolated hyponatremia was observed in 36(53%) and 15(22%) had isolated hypokalaemia. Both hyponatremia and hypokalaemia was found in 17(25%) cases. The mean serum sodium level was (133.82±2.52) mmol/l. Among patients with isolated hyponatremia, 24(67%) had mild hyponatremia and 12(33%) got moderate hyponatremia. Again the mean serum potassium was (3.45±0.23) mmol/l. Among patients with isolated hypokalaemia, 10(67%) had mild hypokalaemia and 5(33%) had moderate hypokalaemia. Both hyponatremia and hypokalaemia was observed in one fourth of total electrolytes depleted cases and all were within the mild range. No patient had severe hyponatremia or hypokalaemia. Faridpur Med. Coll. J. Jan 2020;15(1): 24-27